Reproductive effort and future parental competitive ability: A nest box removal experiment. Issue 17 (11th August 2018) - Fokkema, Rienk W.; Ubels, Richard; Both, Christiaan; de Felici, Livia; Tinbergen, Joost M.
Abstract: The life history trade‐off between current and future reproduction is a theoretically well‐established concept. However, empirical evidence for the occurrence of a fitness cost of reproduction is mixed. Evidence indicates that parents only pay a cost of reproduction when local competition is high. In line with this, recent experimental work on a small passerine bird, the Great tit ( Parus major ) showed that reproductive effort negatively affected the competitive ability of parents, estimated through competition for high quality breeding sites in spring. In the current study, we further investigate the negative causal relationship between reproductive effort and future parental competitive ability, with the aim to quantify the consequences for parental fitness, when breeding sites are scarce. To this end, we (a) manipulated the family size of Great tit parents and (b) induced severe competition for nest boxes among the parents just before the following breeding season by means of a large‐scale nest box removal experiment. Parents increased their feeding effort in response to our family size manipulation and we successfully induced competition among the parents the following spring. Against our expectation, we found no effect of last season's family size on the ability of parents to secure a scarce nest box for breeding. In previous years, if detected, the survival cost of reproduction was always paid after midwinter. In this year, parents did pay a survival cost of reproduction before midwinter and thus before the onset of the experiment in early spring. Winter food availability during our study year was exceptionally low, and thus, competition in early winter may have been extraordinarily high. We hypothesize that differences in parental competitive ability due to their previous reproductive effort might have played a role, but before the onset of our experiment and resulted in the payment of the survival cost of reproduction. Abstract : The trade‐off between current and future reproduction may be mediated by a negative causal relationship between reproductive effort and future parental competitive ability. To test this, we (a) manipulated the family size of great tit ( Parus major ) parents and (b) induced severe competition for nest boxes among the parents just before the following breeding season by means of a large‐scale nest box removal experiment. We found no effect of experimental family size on the likelihood of parents to claim scarce breeding boxes the following spring, but did detect a survival cost of reproduction before the onset of our experiment.